Role of Long Noncoding RNA Dio3os in Glycolipid Metabolism - Wang, Xinchen; Zeng, Shiyun; Liu, Yuting; Shi, Yulan; Qu, Fenghua; Li, Li; Zhang, Qirui; Yuan, Ding; Yuan, Chengfu (Current Genomics, 2025)
IntroductionRecent investigations have underscored the importance of long non-coding RNAs (lncRNAs), which exhibit more specific expression in tissues and cells than mRNA and are involved in gene regulation during development, pathology, and other processes through various mechanisms. Despite the predominant focus on the role of lncRNA Dio3os in cancer research, there has been relatively limited exploration of its potential involvement in glycolipid metabolism. Therefore, this study aims to consolidate existing knowledge on the function of Dio3os in glycolipid metabolism and calls for a broader investigation into its physiological roles.MethodsThis review synthesizes available literature to detail the gene characteristics of lncRNA Dio3os and its expression patterns. It also compiles recent insights and mechanisms pertaining to Dio3os's involvement in glycolipid metabolism, particularly its participation in the ceRNA regulatory network.ResultsRecent studies demonstrate that lncRNA Dio3os regulates glycolysis in cancer cells and impacts obesity, potentially serving as an indicator for diabetic peripheral neuropathy. Furthermore, its diminished expression has been noted in atherosclerotic plaques.ConclusionlncRNA Dio3os exerts a significant regulatory influence on glycolipid metabolism, with variations in its expression levels potentially affecting disease presentations. Further investigations are warranted to elucidate the precise relationship between lncRNA Dio3os and its associated pathologies.
Keywords: diabetic peripheral neuropathy